2011
DOI: 10.1074/jbc.m111.240267
|View full text |Cite
|
Sign up to set email alerts
|

ERp29 Regulates ΔF508 and Wild-type Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Trafficking to the Plasma Membrane in Cystic Fibrosis (CF) and Non-CF Epithelial Cells

Abstract: Sodium 4-phenylbutyrate (4PBA) improves the intracellular trafficking of ⌬F508-CFTR in cystic fibrosis (CF) epithelial cells. The underlying mechanism is uncertain, but 4PBA modulates the expression of some cytosolic molecular chaperones. To identify other 4PBA-regulated proteins that might regulate ⌬F508-CFTR trafficking, we performed a differential display RT-PCR screen on IB3-1 CF bronchiolar epithelial cells exposed to 4PBA. One transcript up-regulated by 4PBA encoded ERp29, a luminal resident of the endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 70 publications
1
43
0
Order By: Relevance
“…We recently demonstrated that one 4PBA-regulated species identified in this screen, ERp29 (endoplasmic reticular protein of 29 kDa), is a novel chaperone of the endoplasmic reticulum that promotes the trafficking of wt and ⌬F508 CFTR, the first such luminal chaperone to have this role (10). We also, as described here, identified Elp2 as a potential 4PBA-stimulated regulator of Hsp70.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We recently demonstrated that one 4PBA-regulated species identified in this screen, ERp29 (endoplasmic reticular protein of 29 kDa), is a novel chaperone of the endoplasmic reticulum that promotes the trafficking of wt and ⌬F508 CFTR, the first such luminal chaperone to have this role (10). We also, as described here, identified Elp2 as a potential 4PBA-stimulated regulator of Hsp70.…”
Section: Discussionmentioning
confidence: 83%
“…Differential Display RT-PCR Screen-Differential display RT-PCR was performed using the RNAimage™ kit (Genhunter) on total RNA isolated from IB3-1 cells treated with 1 mM 4PBA for 0, 4, 8, or 24 h as previously described in detail (10). Differentially expressed cDNAs were extracted, re-amplified by PCR, and cloned into pCRII (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the chemical chaperone sodium 4-phenylbutyrate (4-PBA) improves traffi cking of both D F508-and wild-type CFTR in bronchial epithelial cells. 18 Furthermore, selective inhibition of ERAD through interference with valosin-containing protein (VCP), a component of the ER export and proteasomal degradation machinery, was shown to rescue D F508-CFTR from ERAD and increase its cell surface expression in human bronchial epithelial cells. 19 Further research is necessary to develop treatment strategies centered on resolving misfolding events and/or regulating the UPR to correct for CF lung disease.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…ERp29 is a chaperone expressed in the endoplasmic reticulum, where it facilitates the processing and transport of proteins. Its chaperone activity underpins numerous biological functions, including roles in virus infections, cystic fibrosis, and tumor suppression and treatment (Rainey-Barger et al, 2009;Das et al, 2009;Farmaki et al, 2011;Suaud et al, 2011;Zhang and Richardson, 2011;Bambang et al, 2013;Wu et al, 2012). The 3D structure of the C-terminal domain of rat ERp29 was first determined by NMR spectroscopy using the conventional NOE approach.…”
Section: Introductionmentioning
confidence: 99%